Geochemical features of holocene section of Minzelinskoe lake sapropel (Western Siberia) - Anton Maltsev; Galina Leonova; Vladislav Bobrov; Sergey Krivonogov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Sapropel is biogenic lake sediment. It mainly consists of photosynthetic aquatic plants residues, and it is the important carbon storage. Therefore, the study of sapropelic lakes has not only theoretical but also applied value (agriculture, chemical industry, medicine). The main aim of the study: investigation of the matter and chemical composition of the fivemeter long sediment core of Lake Minzelinskoe, Novosibirsk region, obtained in the central part of the lake. Methods used in the study: atomic absorption analysis, atomic emission spectrometry with inductively coupled plasma, Xray fluorescence analysis, CHNS elemental analysis, sowing and counting microorganisms, radiocarbon dating, silicate Xray fluorescence and Xray diffraction analysis, highresolution gammaspectrometry a semiconductor using a HPGe detector, loss on ignition, dfissolution of carbonates, titrimetric, turbidimetric and photometric methods. Results: It was ascertained that during the last 6000 years organicmineral deposits of Lake Minzelinskoe have been formed (the Holocene). They consist of two layers: macrofitogenic sapropel (0-290 cm) and peaty sapropel (290-460 cm). The lake developed in twostages: first, it was formed as swampy lowland and then became a lake. The ratios of mineral to organic portions of the sediment are 40 and 60 % (interval 0-25 cm), 30 and 70 % (25-400 cm), and 20 and 80 % (400-450 cm), respectively. For 6000 years 13,8 g/cm2of carbon was accumulated: in macrophyte layer - 6,7 g/cm2, in peaty - 7,07 g/cm2, with an average speed of carbon receipt 23 mg/cm2 per year. Unequal enrichment of different sediment layers by chemical elements reflects the changes in vegetation types and related biochemical reactions. Despite the layer differences, their chemical composition is rather stable, and it shows economic usability of the Lake Minzelinskoe sapropels